2016
DOI: 10.4238/gmr.15038218
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of breast cancer in individuals carrying the TNRC9 rs3803662 C>T polymorphism: a meta-analysis of case-control studies

Abstract: ABSTRACT. Currently, the relationship between the trinucleotide repeat containing 9 (TNRC9) rs3803662 C>T polymorphism and risk of breast cancer (BC) is uncertain. Here, we attempted to obtain a more accurate assessment of this association by conducting a meta-analysis of all eligible case-control investigations, comprising 44,820 cases and 58,316 controls. A comprehensive search was performed to identify all suitable studies involving the TNRC9 rs3803662 polymorphism and BC risk. Pooled odds ratios (ORs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…The two remaining SNPs, rs2046210 and rs3803662, were found to be associated with breast cancer risk in our Vietnamese cohort, with P values less than 0.007 (Table 6). In addition, these results correlate with other association studies of rs2046210 and rs3803662 in Europeans and Asians, especially Japanese, with P values less than 0.03 and the highest OR (95% CI) being 2.16 (1.32-3.59) (Cai et al, 2011;Mizoo et al, 2013;Mazhar et al, 2016;Wang et al, 2016;Hu et al, 2017). Therefore, these two SNPs are likely to increase the risk of breast cancer up to two-fold in Vietnamese women (Tables 7 and 8), as in other ethnic groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The two remaining SNPs, rs2046210 and rs3803662, were found to be associated with breast cancer risk in our Vietnamese cohort, with P values less than 0.007 (Table 6). In addition, these results correlate with other association studies of rs2046210 and rs3803662 in Europeans and Asians, especially Japanese, with P values less than 0.03 and the highest OR (95% CI) being 2.16 (1.32-3.59) (Cai et al, 2011;Mizoo et al, 2013;Mazhar et al, 2016;Wang et al, 2016;Hu et al, 2017). Therefore, these two SNPs are likely to increase the risk of breast cancer up to two-fold in Vietnamese women (Tables 7 and 8), as in other ethnic groups.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to these association studies, many metaanalyses have been conducted to increase statistical power, to resolve conflicting results between individual studies, and to improve estimates of the size of the effect (Hunter and Schmidt, 1990). The results have demonstrated consistency, with all seven SNPs shown to be significantly associated with an increased risk of breast cancer among different ethnic groups, including Asians and Europeans, with P values lower than 0.03 and OR (95% CI) values ranging from 1.07 (1.01 -1.13) to 1.62 (1.44 -1.83) (Wang et al, 2013;Zheng et al, 2014;Tang et al, 2016;Wang et al, 2016;Yang et al, 2016;Zhang et al, 2016;Hu et al, 2017). Interestingly, two SNPs, rs889312 and rs13281615, were shown not to be associated with breast cancer risk in Africans (Zheng et al, 2014;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 80%
“…20 Moreover, studies have confirmed that TOX3 methylation abnormalities may be closely related to the occurrence of PCOS and may play a role in the development of PCOS pathology by regulating changes in TOX3 protein expression. 20,22 The SNP rs3803662 C>T also shows significant associations with estrogen receptor status, 23 and patients with PCOS have a higher risk of spontaneous abortion. 20,22 The SNP rs3803662 C>T also shows significant associations with estrogen receptor status, 23 and patients with PCOS have a higher risk of spontaneous abortion.…”
Section: Introductionmentioning
confidence: 97%
“…12 Studies have shown that the genetic variants in the TOX3 gene are associated with multiple diseases, including lung cancer, familial ovarian cancer, polycystic ovary syndrome (PCOS), and breast cancer, [13][14][15][16][17][18][19] and Wang Q et al found that the rs3803662 C>T polymorphism is strongly related to an increased risk of breast cancer in both Asian and Caucasian populations. 20 Moreover, studies have confirmed that TOX3 methylation abnormalities may be closely related to the occurrence of PCOS and may play a role in the development of PCOS pathology by regulating changes in TOX3 protein expression. 21 In recent years, studies have confirmed that rs3803662 C>T is the most important genetic variation in the TOX3 locus, which is associated with an increased risk of breast cancer in women.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation